Spatial effects on the aggregate demand - Fernando Barreiro-Pereira (European Regional Science Association (ERSA), 2002)
This paper analyses if several spatial variables coming from cities and transportation system can affect the money market, specially the income velocity of circulation. The specification of the theoretical model include the income velocity of circulation into the IS-LM multipliers. Considering the Baumol-Tobin model for transaction money demand, the Central Place Theory, and some gravity models, we can conclude that the incom velocity of circulation and the supply money in monetary terms are dependent, among others, of seven spatial variables such as the country first city population, the population density, the passenger-kilometers transported by railways, and several ratios referred to some geographical variables. The model has been applied across 64 countries during the period 1978-1997. Panel data techniques has been used for estimating the model. Thresults indicate that most of the explanatory variables are significant on income velocity of circulation and the money supply. The macroeconomic equilibriunm is affected by the spatial explanatory variables because these last affect the LM curve, an hence prices and output level maybe influenced because of that.
Keywords: 330